The relationship between physical activity level on the severity of dysmenorrhea - Trisnowiyanto, Bambang; Andriani, Isna (Jurnal Keolahragaan, 2024)
Dysmenorrhea is a disorder in which women experience pain or cramping in the abdominal region throughout the menstrual cycle. It has been noted that physical activity and psychological variables can exacerbate dysmenorrhea. The purpose of this study was to examine the association between  physical activity level and the severity of dysmenorrhea in late adolescence. This cross-sectional study involved 126 late female adolescents aged 17 to 25 years experiencing dysmenorrhea. The independent variable was physical activity, which was measured using the International Physical Activity Questionnaires (IPAQ), categorized into high and low physical activity levels . The dependent variable was dysmenorrhea, measured using the working ability, location, intensity, days of pain, and dysmenorrhea (WaLIDD), which was categorized into severe and mild dysmenorrhea. The association between physical activity  and dysmenorrhea was analysed using simple binary logistic regression analysis.The findings indicated that mild dysmenorrhea was 93.65% and severe dysmenorrhea was 6.35%. Adolescents who engage in high physical activity were more likely to experience severe dysmenorrhea than adolescents who engage in light physical activity (OR= 5.11; p= 0.032; 95% CI= 1,15 to 22,72). The probability of adolescents who participated in high physical activity in experiencing severe dysmenorrhea was 14.70%. It can be concluded that high physical activity level is correlated to higher risk of experiencing severe dysmenorrhea.